Family Meanings in Perunggu's '33X' Music Video: The Study of Semiotic Analysis Roland Barthes - Dharma, I. Komang Oka; Pratami, Febryanti; Sadiyyah, Zulfanida Nurul (Yayasan Sinergi Kawula Muda, 2024)
This research was conducted with the objective of analyzing the representation of the meaning of kinship in the music video of the band Perunggu entitled